PENGARUH PENDAPATAN ASLI DAERAH (PAD), DANA ALOKASI UMUM (DAU) DAN DANA ALOKASI KHUSUS (DAK) TERHADAP BELANJA MODAL PADA KABUPATEN / KOTA ( STUDI KASUS DI PROVINSI JAWA BARAT, JAWA TENGAH DAN JAWA TIMUR PERIODE TAHUN 2007 â 2010 ) - Ainur Rofiq, Mohamad (Students Journal of Economic and Management, 2012)
This research was hold to examine the influence of Local Government Original Receipt, the General Allocation Fund, and the Special Allocation Fund on Capital Expenditures with a case study on the district / city in the province of West Java, Central Java and East Java, and to know comparison of the influence of Local Government Original Receipt, the General Allocation Fund, and the Special Allocation Fund on Capital Expenditures in the third against the province. The data used in this study is a secondary data annual time series (Time Series) 2007 s / d 2010. The data analysis technique used is multiple linear regression to test hypotheses using t-statistics and goodness of fit testing using the F-statistic models. The results provide information that: (1) In the province of West Java, local government original receipt has a positive and significant effect on capital expenditures, while the General Allocation Fund, and the Special Allocation Fund had no significant effect on capital expenditures. (2) In the province of Central Java, the General Allocation Fund has a positive and significant effect on capital expenditures, while the Special Allocation Fund has a negative and significanteffect on capital expenditures but local government original receipt does not have a significant effect on capital expenditures. (3). In the province of East Java, local government original receipt and the General Allocation Fund have a positive and significant effect on capital expenditures, while DAK had no Receipt to Capital Expenditures in the province of West Java are stronger than in Central Java and East Java, with the value of the standardized coefficient of 0.607 and significant at the Central Java province of 0.120 and 0.261 of East Java province. (5) influencet of the General Allocation Fund on capital expenditures in the province of East Java is stronger than the Province of West Java and Central Java to the value of the standardized coefficient of 0.500 and significant at the West Java province of 0.101 and 0.411 of Central Java Province. (6) Influence the Special Allocation Fund of against Capital Expenditure in the province of Central Java is stronger than the Province of West Java and East Java, with the value of the standardized coefficient of -0.200 and significant, while in West Java province of 0.118 and -0.084 for Central Java Province. Keywords: Local Government Original Receipt, the General Allocation Fund, the Special Allocation Fund, and Capital Expenditure